Introduction to hydrocodes - Zukas, Jonas A. (Studies in applied mechanics, 2004)
A hydrocode refers to a computer program used for the study of the dynamic response of materials and structures to impulse (primary blast), impact (involving everything from car and aircraft collisions to impacts of space structures by assorted debris). The understanding of hydrocodes requires knowledge of numerical methods in the code as well as a keen understanding of the physics of the problem being addressed. This can take many years to learn via codes. There are currently a number of titles addressing the physics of high pressure and high rate material but nothing introducing the novice to the fundamentals of this highly technical and complicated study. This title bridges the gap, bringing together the large body of literature, scattered through diverse journals, government and corporate reports and conference proceedings. As valuable as the text are the cited references and the combination will take years off the preparation time of future code users. * Introduces complex physics essential for the understanding of hydrocodes * Infused with over 30 years practical experience in the field * Brings together a wide range of literature saving valuable research time.